2016
DOI: 10.3109/0284186x.2015.1115121
|View full text |Cite
|
Sign up to set email alerts
|

Trends in kidney cancer among the elderly in Denmark, 1980–2012

Abstract: A challenge in managing kidney cancer in the elderly is to establish interdisciplinary collaborations between different specialties, such as surgeons, clinical oncologists, and geriatricians to be able to deliver the best possible care in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
(14 reference statements)
2
15
1
Order By: Relevance
“…Fixed multivariable regression models were used to estimate clinical outcomes according to each concomitant medication category following adjustment for preplanned adjusting covariates that might represent confounders. [22][23][24] The key covariates were: primary tumor type (NSCLC, melanoma, renal cell carcinoma and others), age (<70 vs ≥70 years), [25][26][27][28] sex (male vs female), Eastern Cooperative Oncology Group-Performance Status (ECOG-PS) (0-1 vs ≥2), burden of disease (number of metastatic sites≤2 vs >2), treatment line (first vs non-first) and BMI. BMI was used given to its alleged role in affecting immunotherapy clinical outcomes 15 16 and as a surrogate of cardiovascular/ metabolic conditions which might have influenced the prescription of certain concomitant medications.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…Fixed multivariable regression models were used to estimate clinical outcomes according to each concomitant medication category following adjustment for preplanned adjusting covariates that might represent confounders. [22][23][24] The key covariates were: primary tumor type (NSCLC, melanoma, renal cell carcinoma and others), age (<70 vs ≥70 years), [25][26][27][28] sex (male vs female), Eastern Cooperative Oncology Group-Performance Status (ECOG-PS) (0-1 vs ≥2), burden of disease (number of metastatic sites≤2 vs >2), treatment line (first vs non-first) and BMI. BMI was used given to its alleged role in affecting immunotherapy clinical outcomes 15 16 and as a surrogate of cardiovascular/ metabolic conditions which might have influenced the prescription of certain concomitant medications.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…The following clinical factors were evaluated: BMI (obese, overweight, normal weight, underweight), primary tumor (NSCLC, melanoma, kidney and others), age (<70 vs ≥70 years old) [19][20][21][22] , sex (male vs female), Eastern Cooperative Oncology Group Performance Status (ECOG-PS) (0-1 vs ≥2), burden of disease (number of metastatic sites ≤2 vs >2) and treatment line (first vs non-first). In order to properly weighing the impact on clinical outcomes and to find appropriate covariates, the correlations between SMI and SMD (according the study cut offs) and baseline clinical factors (primary tumor, age, ECOG-PS, burden of disease and treatment line) were evaluated with the chi-square test.…”
Section: Methodsmentioning
confidence: 99%
“…Data from NORDCAN showed that the proportion of patients diagnosed with kidney cancer over the age of 70 years has decreased from 43% in 1980 to 32% in 2012 in men and remained almost constant in women, around 50%. Incidence rates were at least five times higher in men aged 70 years or more but there was no particular trend with time (Azawi et al 2016). In men aged less than 70 years, the incidence rates started increasing around 2000.…”
Section: Kidney Cancermentioning
confidence: 84%
“…More patients with metastatic kidney cancer are now being offered systemic treatments with metastatic disease. A recommendation of dose modification for elderly patients with metastatic kidney cancer is needed (Azawi et al 2016) and TKI or mTOR treatments should be offered to elderly patients on the same terms as younger patients. The study concludes that when managing kidney cancer in the elderly it is essential to establish interdisciplinary collaborations between different specialties, such as surgeons, clinical oncologists, and geriatricians, to be able to deliver the best possible care in the future.…”
Section: Kidney Cancermentioning
confidence: 99%